Physical Education in Babylon A Historical Perspective on the Impact of Sports in Ancient Iraqi Society - Mohamed Ahmed Hassan (Jurnal Pengabdian Indonesia, 2025)
Investigation of the role of physical education in the Babylonian civilization is the focus of this research. The primary purpose of this research is to determine, through analysis, the impact of sports, described in this research as a means of education and socialization in order to avoid the view of sports as recreation alone, on achieving this goal. This research uses a descriptive analytical methodology in order to identify the nature of physical activities by investigation of cuneiform writings, images, and archaeological finds. The findings show that sports during the period of the Babylonians represented a necessary aspect of religious rituals, where power-lossexercise and endurance races represented blessings from gods. Large-group sports such as wrestling, hunting, and endurance races served as agents for socialization, instilling discipline, bravery, and teamwork among the youths. Physical education was also a key social trait that ensured military readiness, hence social stability. Therefore, it is important to conclude that the role of physical education in the Babylonian culture was not marginal but a core element that defined identity and the values of the group through moral standards. The relevance and contribution of the Babylonian physical education shed insights into modern debates on physical education through the understanding of the relationship that exists and existed in the past between physical culture and physical education. The contribution of the work is in its approach to the developmental aspect of Mesopotamian sports.